Developing next-generation countermeasures for homeland security threat prevention - Dawson, Maurice 1982-; Kisku, Dakshina Ranjan; Gupta, Phalguni; Sing, Jamuna Kanta; Li, Weifeng (Advances in information security, privacy, and ethics (AISPE) book series, 2016)
This book provides relevant theoretical frameworks and empirical research outlining potential threats while exploring their appropriate countermeasures, offering a broad perspective, from network security, surveillance, reconnaissance, and physical security